Novelty in Colorectal Cancer Biomarkers: The Predictive Value and Clinical Utility of the Carcinoembryonic Antigen and Aldehyde Dehydrogenase 1B1 Autoantibodies for Assessing Tumour Biology and the Cancer Stem Cell Burden - AL-Heyali, Hiba A.M.; AL-Allaf, Rojan G.M. (Asian Pacific Journal of Cancer Biology, 2025)
Background: Colorectal cancer (CRC) is responsible for nearly 10% of cancer cases and deaths and is emerging as one of the most prominent malignant diseases worldwide. Carcinoembryonic antigen (CEA) is the most widely used serum biomarker for CRC, but its limited sensitivity and specificity highlight the need for additional diagnostic and prognostic markers. The mitochondrial enzyme aldehyde dehydrogenase 1B1 (ALDH1B1) is highly expressed in CRC and cancer stem cells (CSCs), representing a novel biomarker, especially as its overexpression triggers an autoantibody response detectable in a patient’s serum. This study aims to quantify serum concentration of CEA and ALDH1B1 autoantibodies in patients with colorectal cancer (CRC) and to investigate the relationship between them. It further seeks to evaluate their prognostic potential as circulating biomarkers for CRC. The underlying hypothesis proposes that elevated CEA and ALDH1B1 autoantibody levels are positively correlated and collectively reflect the underlying cancer stem cell (CSC) burden. This correlation is assessed through a predictive equation developed in the study, providing a novel, noninvasive indicator of tumor progression and aggressiveness. Method: Blood samples were collected from 75 newly diagnosed CRC patients (stages II–IV) and 25 healthy controls. CEA and ALDH1B1 autoantibodies were measured using ELISA techniques. Statistical analyses include analysis of variance (ANOVA), paired t-tests, Duncan’s test, regression analysis, and receiver operating characteristic (ROC) curve assessments using SPSS software. Results: The findings show significantly higher CEA and ALDH1B1 autoantibody levels in CRC patients compared to the controls, though neither marker varied significantly across tumour stages, emphasising their role as indicators of tumour biology rather than tumour burden. The regression analysis revealed a significant direct relationship between CEA and ALDH1B1 autoantibody levels (β = 0.026, p < 0.001), as CEA explains 87% of the variability in ALDH1B1 autoantibody levels. The ROC analysis indicated a good diagnostic performance for CEA (AUC = 0.88) and a fair performance for ALDH1B1 autoantibodies (AUC = 0.67). Conclusion: The strong predictive relationship between CEA and ALDH1B1 autoantibodies suggests that CEA levels may indirectly reflect CSC activity, potentially guiding personalised treatment strategies targeting both bulk tumours and CSCs.